Cryo-EM structure and dynamics of the green-light absorbing proteorhodopsin - Stephan Hirschi (Nature Portfolio, 2021)
The cryo-EM structure of pentameric green-light absorbing proteorhodopsin together with molecular dynamics simulations and functional studies provides insights into the proton translocation pathway and oligomerization, and a protonation-dependent mechanism for intracellular half channel hydration.